1994
DOI: 10.1016/0735-1097(94)90298-4
|View full text |Cite
|
Sign up to set email alerts
|

Underdetection of ventricular tachycardia by algorithms to enhance specificity in a tiered-therapy cardioverter-defibrillator

Abstract: Algorithms to enhance specificity cause underdetection of ventricular tachycardia in a significant minority of patients with tiered-therapy cardioverter-defibrillators. Optimal programming can minimize underdetection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 22 publications
0
55
0
Order By: Relevance
“…Swerdlow et al [11] showed that the sudden onset failed to detect 0.5% of spontaneous VT episodes. Other limitation of the onset criterion is the inability to distinguish paroxysmal ATs with sudden onset.…”
Section: Discussionmentioning
confidence: 99%
“…Swerdlow et al [11] showed that the sudden onset failed to detect 0.5% of spontaneous VT episodes. Other limitation of the onset criterion is the inability to distinguish paroxysmal ATs with sudden onset.…”
Section: Discussionmentioning
confidence: 99%
“…19 Programming the AICDs to a higher detection rate reduces the sensing and misinterpretation of atrial arrhythmias as ventricular arrhythmias. 13 But, this could lead to potential under detection of relatively slow monomorphic VTs, polymorphic ventricular arrhythmias or ventricular fi brillation due to intermittent undersensing. 13 Use of dual-chamber devices have shown to decrease the odds of inappropriate detection when compared to single-chamber detection.…”
Section: Minimizing Inappropriate Shocksmentioning
confidence: 99%
“…There is a theoretical risk of under detection of true malignant ventricular arrhythmias, but current data suggest that such under detection is infrequent. 12,13 The effectiveness of such discriminator is reduced when atrium fi res at rates more than 170/min.…”
Section: Minimizing Inappropriate Shocksmentioning
confidence: 99%
“…Patient-related factors include rate-dependent bundle branch block during SVT and exercise-induced myopotentials in sinus tachycardia [24]. Algorithmrelated factors include misalignment of the sinus template with the tachycardia electrocardiogram, clipping of high-amplitude electrocardiograms, electrocardiogram changes during lead maturation, and shock-induced electrocardiogram changes [25].…”
Section: Single-chamber Svt-vt Discriminatorsmentioning
confidence: 99%